Development of teaching guides using collaborative tools in Library and Information Science courses - Calvo Sánchez, Loirette (2015)
This investigation is a descriptive study carried out by the School of Library and Information Science of the UCR. It addresses the rules for the development of a teaching guide for the area of data processing, including the design and contents selection that constitute the internal and external schema structure that should be presented to the students, and the way in which tools as Goanimate and Glogster can be integrated in their development. This scientific article includes the theory and methodology used in the research and evaluation applied to the tutorial.